A profile of the rural poor projects of BRDB - Quashem, M. A.; Fazlul Bari, A. K.; BRDB Institutional Support Project (Dhaka : BRDB Institutional Support Project, 1999)
With reference to anti-poverty projects and programs undertaken by Bangladesh Rural Development Board.
Keywords: Economic assistance, Domestic -- Bangladesh; Rural development projects -- Bangladesh